Mobile Internet and the Rise of Political Tribalism in Europe - Marco Manacorda; Guido Tabellini; Andrea Tesei (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the political effects of the diffusion of mobile Internet between 2007 and 2017, using data on electoral outcomes and on mobile Internet signal across the 84,564 municipalities of 22 European countries. We find that access to mobile Internet increased voters' support for right-wing populist parties and for parties running on extreme socially conservative platforms, primarily in areas with greater economic deprivation. Using survey data, we also show that mobile Internet increased communitarian attitudes, such as nationalism and dislike of strangers and minorities. We conclude that mobile Internet benefitted right-wing populist parties because, in line with findings in social psychology, it fostered offline tribalism.
Keywords: D72; D91; L86; 330; populism; communitarianism; Europe; mobile Internet